The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijms23115872
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Mast Cells and Regulatory T Cells in Immune-Mediated Cholangiopathies

Abstract: Immune-mediated cholangiopathies are characterised by the destruction of small and large bile ducts causing bile acid stasis, which leads to subsequent inflammation, fibrosis, and eventual cirrhosis of the liver tissue. A breakdown of peripheral hepatic immune tolerance is a key feature of these diseases. Regulatory T cells (Tregs) are a major anti-inflammatory immune cell subset, and their quantities and functional capacity are impaired in autoimmune liver diseases. Tregs can undergo phenotypic reprogramming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 126 publications
0
2
0
Order By: Relevance
“…Overall, therefore, the interplay between Treg and MC is clearly complex with diverse potential outcomes, necessitating further, context-dependent research before it can be directly exploited for therapeutic purposes. A recent comprehensive review focused on therapeutic opportunities for cholangiopathies provides a more detailed delineation of Treg/MC cross talk (72).…”
Section: Granulocytesmentioning
confidence: 99%
“…Overall, therefore, the interplay between Treg and MC is clearly complex with diverse potential outcomes, necessitating further, context-dependent research before it can be directly exploited for therapeutic purposes. A recent comprehensive review focused on therapeutic opportunities for cholangiopathies provides a more detailed delineation of Treg/MC cross talk (72).…”
Section: Granulocytesmentioning
confidence: 99%
“…[8] A comprehensive overview of MC contribution to the progression of liver diseases, including cholestatic disease, was recently reviewed here [14,15]. Although the interactions between MCs and innate immune cells to promote the adaptive immune response [16] and regulatory T cells during cholangiopathies [17] have been well described, there is little known about the interactions that MCs have with other innate immune cells during cholestasis. The purpose of this review is to describe previously identified MC-innate immune cell interactions, which may play a role, directly or indirectly, in cholestatic liver diseases.…”
Section: Accepted Manuscriptmentioning
confidence: 99%